If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(8z + -5) = 0 Reorder the terms: 9(-5 + 8z) = 0 (-5 * 9 + 8z * 9) = 0 (-45 + 72z) = 0 Solving -45 + 72z = 0 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '45' to each side of the equation. -45 + 45 + 72z = 0 + 45 Combine like terms: -45 + 45 = 0 0 + 72z = 0 + 45 72z = 0 + 45 Combine like terms: 0 + 45 = 45 72z = 45 Divide each side by '72'. z = 0.625 Simplifying z = 0.625
| 6(x+1)=3(x-6) | | 5x+2(x+10)=83 | | 6x+5x-2x+17x=117 | | -5.6=y-8 | | a+5+8=20 | | c=210+c | | 9(8z-5)= | | x+8=57 | | d=.75d | | 9x-14=7x+22 | | 3.16=-6n-2n | | (8)(-5)= | | -2(y+1)=16 | | 2.8=-(x+4) | | y^2+12y+17=0 | | 7.21=2*3.14r | | -6(x+10)=-24 | | -15+7-(-15)= | | 24x=50-6 | | 7.21=3.14r | | 6=2n-8 | | t=5t-2(t+2) | | 3x-7+2x=4x+3 | | 6x+3x=99 | | 2u^2-16u+31=(u-6)(u-6) | | -2.5=q-1.7 | | -4(4x+5)=-6-2(8x+7) | | 220=.5h*44 | | 2.5x-12x-7=108 | | 15x=y+400 | | 5x+5=100 | | 12+8-15=-2(3x-82) |